Hydroxychloroquine in the treatment of COVID-19 disease: a systematic review and meta-analysis (Medical Journal of Indonesia, 2021)
BACKGROUND Given the urgency of finding a specific treatment for coronavirus disease 2019 (COVID-19), several approaches have been carried out, including the use of chloroquine (CQ) and hydroxychloroquine (HCQ). This study was aimed to systematically evaluate the available evidence on the effectiveness of HCQ in the treatment of COVID-19 disease. METHODS We searched 3 databases (PubMed, Google Scholar, and ClinicalTrials) until May 31, 2020 for clinical studies in patients diagnosed with COVID-19 comparing conventional treatment with and without HCQ combined with or without azithromycin. The risk of bias assessment and quality evaluation was carried out according to the Cochrane recommendations. RESULTS 5 articles (1 randomized clinical trial [RCT], 1 non-RCT, and 3 cohort studies) were included. The main outcome measure in 2 articles was the virological conversion determined by reverse transcription-polymerase chain reaction; however, the findings of both studies were contrary. The main objective of the other studies was to determine the effects of HCQ on COVID-19 mortality, and the studies showed similar results. In general, the studies showed methodological limitations, risk of bias, and variable quality. A meta-analysis from 2,041 patients showed the odds ratio of mortality for patients having HCQ and standard care was 1.38 (95% CI 0.93–2.04). CONCLUSIONS Considering the limited data available and the very low-to-moderate quality of the studies included in this systematic review, the evidence suggests that the HCQ administration does not decrease the risk of death from COVID-19.